Maximum Ride : the manga. 9 - Lee, NaRae (Yen Press, 2015)
"When Dr. Martinez and her colleagues established the coalition to stop the madness, spreading environmental awareness through the flock's public air shows, Max knew it could be dangerous. Never in her wildest dreams, though, did she imagine that a criminal mastermind would abduct her mother! Now the flock has to team up with the U.S. Navy to rescue Dr. Martinez...and of course, the world!"--Back cover.